Afrikaner Nationalism in the Political Life of the Union of South Africa in the First Third of the 20th Century - STRELTSOV Alexey Dmitrievich (Ученые записки Института Африки Российской академии наук)
The purpose of the article is to trace the formation and development of Afrikaner nationalism, which played an important role in the political life of the Union of South Africa in the first third of the 20th century; to find out the origins of the formation of Afrikaner nationalism and what factors influenced this formation; to analyze which groups of the white population of the Union of South Africa were close to the ideas of Afrikaner nationalism, to show how Afrikaner nationalism diverged from other ideologies in the Union of South Africa and how it influenced the political life of the dominion, how it influenced the relations of the Union of South Africa with Great Britain and, consequently, the formation of the British Commonwealth.